Carcass Fungistasis of the Burying Beetle Nicrophorus nepalensis Hope (Coleoptera: Silphidae). (24th April 2013) - Hwang, Wenbe; Lin, Hsiu-Mei
Abstract : Our study investigated the fungistatic effects of the anal secretions of Nicrophorus nepalensis Hope on mouse carcasses. The diversity of fungi on carcasses was investigated in five different experimental conditions that corresponded to stages of the burial process. The inhibition of fungal growth on carcasses that were treated by mature beetles before burial was lost when identically treated carcasses were washed with distilled water. Compared with control carcasses, carcasses that were prepared, buried, and subsequently guarded by mature breeding pairs of beetles exhibited the greatest inhibition of fungal growth. No significant difference in fungistasis was observed between the 3.5 g and the 18 to 22 g guarded carcasses. We used the growth of the predominant species of fungi on the control carcasses, Trichoderma sp., as a biological indicator to examine differences in the fungistatic efficiency of anal secretions between sexually mature and immature adults and between genders. The anal secretions of sexually mature beetles inhibited the growth of Trichoderma sp., whereas the secretions of immature beetles did not. The secretions of sexually mature females displayed significantly greater inhibition of the growth of Trichoderma sp. than those of sexually mature males, possibly reflecting a division of labor in burying beetle reproduction.